Privacy-preserving mining of association rules based on paillier encryption algorithm - Huan XING; Lin ZHANG (网络与信息安全学报)
In privacy preserving association rule mining, the precision and security of mining are always a pair of contradictions. A method of privacy-preserving mining of association rules based on paillier encryption algorithm over distributed databases was proposed. The method separated calculation and decryption so it can solve the prob-lem of accuracy and security from mining of association rules perfectly. The method can reduce the time cost by Montgomery reduction. The experiment shows that the time cost on the basis of adding the process of encryption and decryption is acceptable.